Geostatistical analyses of IODP Hole 339-U1386B - Jiawei Pan; Dorrik A V Stow; Zeinab Smillie; Peter Burgess (PANGAEA, 2024)
Shipboard core description and thickness measurements were used as base for the current data. These were verified and, where necessary, minor corrections made during re-logging of all cores used for this study at the Bremen Core Repository. Any modifications to the shipboard core logs were validated by making and examining a further 100 smear slides to measure composition and grain size.
In: Pan, J et al. (2024): Thickness, age and layers data of sediments at IODP Site U1386, U1387, and U1389 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.936132